OCCUPATIONAL ASTHMA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Occupational asthma makes it hard to breathe when you work with substances that cause your airways to swell. It can cause shortness of breath, a cough and chest tightness that usually get better when you’ve been away from work for a while. Treatments can help, but the best way to reduce your risk of an asthma attack is to avoid triggers.